An investigation into teachers’ perspectives on the implementation of environmental concepts in life orientation in grade 9 : a Western Cape case study - Dirks, Leonora Michelle (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.